Analisis Perhitungan Cost-Volume-Profit Sebagai Alat Bantu Perencanaan Laba Perusahaan - Maharany, Indah Dewi; Hidayah, Nurul (Eqien - Jurnal Ekonomi dan Bisnis, 2025)
The aim of the research is to determine the Cost-Volume-Profit analysis of Furniture UMKM in Jepara. This type of research is in the form of quantitative data, namely the amount of expenses that will take place during 2023. The results of the analysis show that the company has a contribution margin of IDR 1,984,576,347 with a ratio of 25%, indicating that every IDR 1 of sales contributes 25% to cover fixed costs and profits. The break-even point was recorded at IDR 6,948,262,151, indicating that from total sales of IDR 7,876,000,000, IDR 6,948,262,151 was needed to reach break-even. The Margin of Safety reached IDR 927,737,849, providing room for the company to experience a sales decline of that size without experiencing a loss. Degree of Operating Leverage reaching 7.25 indicates high sensitivity of operating profit to changes in sales. Profit target analysis shows that the company needs to achieve sales of IDR 8,178,867,936 to obtain the expected profit of IDR 240,562,547. The conclusions from this analysis provide a basis for companies to plan more optimal profit targets to ensure business sustainability in the coming year.